2020
DOI: 10.2166/wpt.2020.118
|View full text |Cite
|
Sign up to set email alerts
|

Reusability performance of green zinc oxide nanoparticles for photocatalysis of bathroom greywater

Abstract: This study aims to investigate the potential of green zinc oxide nanoparticles (ZnO NPs) in reusability performance for photocatalysis of bathroom greywater. It was found that ZnO NPs photocatalytic treatment of real bathroom greywater (RBGW) effluent reduces both the COD and BOD5 concentrations by 72.01, 62.75 and 57.79% (COD) and 70.18, 60.32 and 57.56% (BOD5) respectively for the first, second and third cycle. Meanwhile for the photocatalysis of ABGW, it was observed that COD and BOD5 were removed by 82.27,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The pH drift method was used to determine the pH PZC value for 10% Hy-Co–ZnO NPs using NaCl (0.1 N) as an electrolyte solution 59 , 60 . Six flasks were filled with 50.0 mL of the 0.1 N NaCl solution, and each was adjusted to pH values (2, 4, 6, 8, 10, and 12) as an initial pH i value.…”
Section: Resultsmentioning
confidence: 99%
“…The pH drift method was used to determine the pH PZC value for 10% Hy-Co–ZnO NPs using NaCl (0.1 N) as an electrolyte solution 59 , 60 . Six flasks were filled with 50.0 mL of the 0.1 N NaCl solution, and each was adjusted to pH values (2, 4, 6, 8, 10, and 12) as an initial pH i value.…”
Section: Resultsmentioning
confidence: 99%
“…A pH pzc close to this last one was obtained for ZnO NPs synthesized by the green route. Yashni et al reported pH pzc values between 8.5 and 9 for ZnO NPs prepared by the green approach using leaf extract of Corriandrum sativum . It is then evident that the pH pzc is strongly dependent on the synthetic route.…”
Section: Resultsmentioning
confidence: 99%
“…Yashni et al reported pH pzc values between 8.5 and 9 for ZnO NPs prepared by the green approach using leaf extract of Corriandrum sativum. 55 It is then evident that the pH pzc is strongly dependent on the synthetic route. In the case of Z−M NCs, even when several reports have been found in the open literature, only a very few include this kind of characterization.…”
Section: ζ-Potentialmentioning
confidence: 99%
“…One potential determinant pertains to the interplay between surface charges and the forms of gold cyanide complexes. Generally, semiconductors demonstrate positive surface charges when the solution pH falls below the PZC value, transitioning to negative surface charges when the solution pH surpasses the values. , However, gold cyanide complexes usually exhibit the stable form [Au­(CN) 2 ] − across a wide pH range at 25 °C and 1 atm . Consequently, the repulsive interaction stemming from the negative surface charge of the ZC sample and the negative charges of the gold cyanide complexes can be negligible in this context.…”
Section: Resultsmentioning
confidence: 99%